Energy-aware IP traffic engineering with shortest path routing - Amaldi, E.; Capone, A.; Gianoli, L.G. (Computer networks (Amsterdam, Netherlands : 1999), 2013)
Internet energy consumption is rapidly becoming a critical issue due to the exponential traffic growth and the rapid expansion of communication infrastructures worldwide. We address the problem of energy-aware intra-domain traffic engineering in networks operated with a shortest path routing protocol. We consider the problem of switching off (putting in sleep mode) network elements (links and routers) and of adjusting the link weights so as to minimize the energy consumption as well as a network congestion measure. To tackle this multi-objective optimization problem with priority (first minimize the energy consumption and then the network congestion), we propose a Mixed Integer Linear Programming based algorithm for Energy-aware Weights Optimization (MILP-EWO). Our heuristic exploits the Interior Gateway Protocol Weight Optimization (IGP-WO) algorithm for optimizing the OSPF link weights so as to minimize the total cost of link utilization. The computational results obtained for eight real network topologies and different types of traffic matrices show that it is possible to switch off a substantial number of nodes and links during low and moderate traffic periods, while guaranteeing that network congestion is low enough to ensure service quality. The proposed approach is also validated on two networks of emulated Linux routers.